(untitled) (ItalianoLinguadue, 2023)
On self-discovery: the role of the learner diary in language learning The present paper focuses on learner diaries as tools to explore the interconnections between language learning, emotions and the learner’s self. Through the analysis of a corpus of diaries it will be shown how reflective writing can encourage learners to investigate their own perceptions, beliefs, and emotions and to reflect on their own evolving identity as learners and users of a foreign language. The analysis of the diaries will focus on four aspects that emerge from learners’ writing: the emotions associated with language learning, the metacognitive dimension of learning, the relationship between self and foreign language and the metaphors used by learners to describe language learning.